Investigating Research Hotspots and Publication Trends of Spinal Stenosis: A Bibliometric Analysis During 2000–2018 - Yang, Keda; Pei, Lei; Wen, Kaicheng; Zhou, Siming; Tao, Lin (Frontiers in Medicine, 2021)
Spinal stenosis is a common disease affecting the elderly, that is present in a various forms. Its high incidence forces researchers to pay more attention and offer countermeasures. We used the Web of Science Core collection and PubMed database to obtain 5606 scientific studies concerning spinal stenosis and the number of publications maintained a roughly increasing trend from 108 in 2000 to 512 in 2018, only declining in 2011. Bibliometric analysis was conducted using the online analysis software CiteSpace and Bibliographic Item CoOccurrence Matrix Builder (BICOMB). The United States maintains academic leadership in this field. The journal SPINE was the most authoritative with 695 articles and an average of 12.73 citations. The exported major MeSH terms were further biclustered with gCLUTO according to co-word analysis to reveal research hotspots including etiology, pathogenesis, clinical manifestation, conservative treatment, operative indication, internal implantation and postoperative complications. After combination, the main topics focused on pathogenesis and surgical treatment. Narrowing causes flavum ligamentum hypertrophy and posterior longitudinal ligament ossification is widely accepted. Additionally, minimally invasive surgery and internal implantation fixation are more valid in the clinic. Refining pathological classification, optimizing surgical methods and instrument properties will be an important future research direction for spinal stenosis.